PROGRAMA DE AVALIAÇÃO DE VENDAS NO VAREJO DE SANTA ROSA: RESULTADOS DO PRIMEIRO TRIMESTRE DE 2009 - Sparemberger, Ariosto; Zamberlan, Luciano; Büttenbender, Pedro L.; Höfler, Cláudio E.; Graef, Nelinho D.; Mallmann, Carla (Salão do Conhecimento, 2013)
Resumo